Visualization task of the ship pitching - Bielskis, Andrius Antanas; Djačkov, Vasilij; Ramašauskas, Olegas; Seselskis, Erikas (Lietuvos matematikos rinkinys, 2004)
In this article the research and algorithms for calculation of longitudinal ship motion are evaluated. The program for ship’s pitching and heaving modelling based of these algorithms is presented. Applying of this makes possible to determine ship’s seakeeping characteristics mostly using data of the ship’s bodyplan. It is created with Visual Lisp programming language what insures good visual results and good combination with the stages of ship design. The application can be used for training of naval architecture and informatics engineering students, and also in research field helping to create analytical models.